1992
DOI: 10.1111/j.1365-3059.1992.tb02459.x
|View full text |Cite
|
Sign up to set email alerts
|

Production and viability of sclerotia from fungicide‐resistant and fungicide‐sensitive isolates of Botrytis cinerea, B. elliptica and B, tulipae

Abstract: Production of sclerotia by isolates of three Botrytis spp. differing in resistance to benzimidazole and dicarboximide fungicides was compared in vitro. Sensitive isolates of B. cinerea and B. tulipae produced fewer sclerotia than benzimidazole‐resistant isolates, but there were no differences in the size of sclerotia within each species. For B. elliptica, sclerotia of dicarboximide‐resistant isolates were larger and less numerous than those of sensitive isolates. Sclerotia from fungicide‐resistant and ‐sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 19 publications
(23 reference statements)
1
3
0
Order By: Relevance
“…Similarly, the resistant BC isolates showed slower growth rates (6.4 mm d −1 ) at 91% of the growth rate of the non‐BC isolates (7.0 mm d −1 ). This is in line with previous research, which found that isolates of Botrytis species with decreased sensitivity to iprodione grew at a slower rate than sensitive isolates (Hsiang and Chastagner, 1991), and that sclerotia of iprodione‐resistant isolates of Botrytis elliptica showed lower survival rates than sensitive isolates (Hsiang and Chastagner, 1992). Raposo et al (2000) reported decreased sclerotia survival for iprodione‐resistant Botrytis cinerea isolates compared with sclerotia of sensitive isolates; however, they did not see differences in mycelial growth.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, the resistant BC isolates showed slower growth rates (6.4 mm d −1 ) at 91% of the growth rate of the non‐BC isolates (7.0 mm d −1 ). This is in line with previous research, which found that isolates of Botrytis species with decreased sensitivity to iprodione grew at a slower rate than sensitive isolates (Hsiang and Chastagner, 1991), and that sclerotia of iprodione‐resistant isolates of Botrytis elliptica showed lower survival rates than sensitive isolates (Hsiang and Chastagner, 1992). Raposo et al (2000) reported decreased sclerotia survival for iprodione‐resistant Botrytis cinerea isolates compared with sclerotia of sensitive isolates; however, they did not see differences in mycelial growth.…”
Section: Discussionsupporting
confidence: 92%
“…3 , sclerotia were observed after 10 dpi for the Δ bcfet1 mutant but not the B05.10 wild-type strain. These structures are required for overwintering, enabling the fungi to survive unfavorable conditions during extended periods of time when temperatures and/or nutrient availability are low ( 46 ). This observation is consistent with a mutant strain bearing a reduced/impaired acquisition of iron.…”
Section: Resultsmentioning
confidence: 99%
“…(1983) showed that soilborne sclerotia of B. cinerea could survive in the field for up to 15 months. Work done by Hsiang & Chastagner (1992) indicated a longer period of survival, with B. cinerea sclerotia buried at 10 and 20 cm in field soil having an average viability of 77% after 18 months. However, Raposo et al.…”
Section: Discussionmentioning
confidence: 99%